Microcurrent therapy as the nonpharmacological new protocol against Alzheimer’s disease - Kim, Eun Ho; Lee, Won Seok; Lee, Jae Hee; Kwon, Dong Rak (Frontiers in Aging Neuroscience, 2024)
Alzheimer's disease (AD) poses an increasing global health challenge and is marked by gradual cognitive deterioration, memory impairment, and neuroinflammation. Innovative therapeutic approaches as non-pharmacological protocol are urgently needed with side effect risk of drugs.Microcurrent therapy, a non-invasive modality involving low-level electrical currents, has emerged as a potential solution to address AD's complex pathogenesis. This study investigates the optimal application of microcurrent therapy as a clinical protocol for AD, utilizing a comprehensive approach that integrates behavioral assessments and neuroinflammation evaluation in a mouse model of dementia. It established an AD mice model via intracerebroventricular (i.c.v.) injection of Aβ peptide. The results reveal that microcurrent therapy holds promise in ameliorating memory impairment and reducing neuroinflammation in AD. Behavioral assessments, including the Novel Object Recognition Test (NOR) and Radial Arm Maze Test (RAM), demonstrated improved cognitive function following microcurrent therapy. Furthermore, microcurrent therapy inhibited expression of neuroinflammatory proteins, including ionized calcium binding adaptor molecule 1 (Iba1), and glial fibrillary acidic protein (GFAP) in current-treated group.Mechanistic insights suggest that microcurrent therapy may modulate neuroinflammation through the regulation of MAPK signaling pathways. This study emphasizes the prospect of microcurrent therapy as a safe and efficacious non-pharmacological strategy for Alzheimer's disease (AD), providing optimism to the countless individuals impacted by this debilitating ailment. These results contribute to the developments of an innovative clinical protocol for AD and recovery from neurological injury, underscoring the significance of investigating unconventional therapeutic approaches for addressing this complex condition.3 Aim: The goal of this manuscript was to find optimal treatment duration for microcurrent stimulation in AD mouse models. 3-, 6-and 12-hours stimulation periods were used to verify efficacy of the treatment.To find the therapeutic effect and optimal treatment time for microcurrent treatment, 3, 6, and 12 hours on Alzheimer's Disease were used.